Implementasi Metode Tartil dalam Pembelajaran Al-Qur’an Hadis di SMP Islam Walisongo Kembaran Kabupaten Banyumas - Wahyu Lestari, Widi (Jurnal Pendidikan Agama Islam, 2025)
The Qur'an and Hadith are two sources that serve as the foundation in Islamic education. Thus, by learning the Qur'an and Hadith, students can understand the contents of the Qur'an. To be able to understand the contents of the Qur'an, the ability to read the Qur'an is needed in accordance with the rules of tajwid science. Therefore, a learning method is needed that is appropriate to the conditions of students and the material to be delivered. This study aims to determine and describe the implementation of the tartil method in learning the Qur'an and Hadith at Walisongo Kembaran Islamic Middle School, Banyumas. The application of this tartil method aims to improve students' reading of the Qur'an in accordance with the rules of tajwid science. This study uses a qualitative approach with a type of field research conducted at Walisongo Kembaran Islamic Middle School, Banyumas Regency. Data were collected through observation, interviews, and documentation. The results of the study indicate that the implementation of the tartil method in learning the Qur'an and Hadith is carried out through three stages, namely the planning stage, the implementation stage, and the evaluation stage. In the planning stage, teachers design lesson plans, determine learning strategies, and select Quranic readings. The implementation stage involves habituation activities to create a conducive atmosphere, and students read the Quran under teacher guidance and direct correction. The evaluation stage is carried out to assess students' Quranic reading abilities.